Dinamika Perbedaan Pemikiran antar Madzhab Hanafi, Maliki, Syafi’i, Hanbali - Nia Darmawati; Muhammad Firdaus; M. Yakub (CV. ITTC INDONESIA, 2025)
This study aims to identify and understand the dynamics of differences in thought between the Hanafi, Maliki, Shafi'i, and Hanbali schools of thought. The research method used in this study is library research. Data was obtained from secondary literature such as books, journals, scientific articles, and related documents. The procedure was carried out in three stages: literature identification, selection based on relevance and quality, and thematic analysis to develop a deep and contextual conceptual synthesis. The research findings indicate that the dynamics of Islamic thought are inseparable from the needs of the Muslim community in responding to the complexity of legal issues following the passing of Prophet Muhammad SAW. The emergence of the four major madhhabs—Hanafi, Maliki, Shafi'i, and Hanbali—is evidence of the development of Islamic thought institutions in formulating diverse methods of ijtihad based on the same legal sources. The methodological differences within each madhhab reflect the intellectual richness of the community, not division. This article examines the historical and methodological background of the formation of madhhabs as a form of adaptation of Islamic law to the socio-political realities of the Muslim community. By understanding the context of these differences, it is hoped that Muslims can respond to diversity of views wisely as a blessing and strength, not as a source of conflict.